2020
DOI: 10.1101/2020.09.02.279703
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell profiling of histone modifications in the mouse brain

Abstract: The development of the mouse central nervous system (CNS) involves coordinated execution of transcriptional and epigenetic programs. These programs have been extensively studied through single-cell technologies in a pursuit to characterize the underlying cell heterogeneity. However, histone modifications pose additional layers of both positive and negative regulation that defines cellular identity. Here we show that the Cut&Tag technology can be coupled with a droplet-based single cell library preparation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…We also demonstrate that AtacWorks can be adapted for crossmodality prediction of transcription factor footprints and ChIP-seq peaks from low-input ATAC-seq. As such, we anticipate this framework may be broadly useful for other deep learning applications in genomics, such as DNase, MNase, ChIP-seq, and the recently-developed method CUT&RUN 20 , which has comparable high-throughput single-cell adaptations 32,33 Finally, the robustness and speed of AtacWorks enable its application to high-throughput single-cell ATAC-seq datasets of heterogeneous tissues. We show that our method can be used on small subsets of rare lineage-priming cells to denoise signal and identify accessible regulatory regions at previously-unattainable genomic resolution.…”
Section: Resultsmentioning
confidence: 99%
“…We also demonstrate that AtacWorks can be adapted for crossmodality prediction of transcription factor footprints and ChIP-seq peaks from low-input ATAC-seq. As such, we anticipate this framework may be broadly useful for other deep learning applications in genomics, such as DNase, MNase, ChIP-seq, and the recently-developed method CUT&RUN 20 , which has comparable high-throughput single-cell adaptations 32,33 Finally, the robustness and speed of AtacWorks enable its application to high-throughput single-cell ATAC-seq datasets of heterogeneous tissues. We show that our method can be used on small subsets of rare lineage-priming cells to denoise signal and identify accessible regulatory regions at previously-unattainable genomic resolution.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the Methods presented in this article, we are maintaining an online protocol to aid the research community in further development and adoption of TEA-seq on the Protocols.io platform ( https://doi.org/10.17504/protocols.io.bqagmsbw ). Additional development could allow simultaneous measurement of additional aspects of cell biology (e.g., CpG sequencing methods, scCUT&Tag; Bartosovic et al, 2020 ), as well as improvements to the modalities in the TEA-seq trio (e.g., s3-ATAC, Mulqueen et al, 2021 ). In direct comparisons of TEA-seq to existing methods (CITE-seq and scATAC-seq), we found that the sensitivity of gene detection was lower and distributions of antibody detections were altered relative to CITE-seq; however, ATAC-seq data quality remained comparable to the standalone assay ( Figure 4—figure supplement 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously demonstrated the ability of methods adapted from CUT&RUN or CUT&Tag to map TFs and histone modifications in single cells (Bartlett et al, 2021;Bartosovic et al, 2020;Carter et al, 2019;Kaya-Okur et al, 2019;Skene and Henikoff, 2017;Wang et al, 2019;Wu et al, 2020;Xiong et al, 2020;Zhu et al, 2021). Critically, in single cell protocols that utilize transposition by Tn5, many of the enzymatic steps and washes can be performed in bulk cell populations, followed by single cell isolation and barcoding using any of several different methods (Bartlett et al, 2021;Bartosovic et al, 2020;Kaya-Okur et al, 2019;Wu et al, 2020). Based in part on these previous advances, we next developed a simple strategy to adapt multi-CUT&Tag to profile multiple chromatin factors in high throughput within the same single cells.…”
Section: Multi-cutandtag Profiling In Single Cellsmentioning
confidence: 99%